En småländsk festdag i början av mars - Ek-Nilsson, Katarina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2023)
It all started on Facebook in 2010, with a suggestion to celebrate the first Thursday of March. The suggestion was posted by a former resident of the town Jönköping. The posters suggestion emanated from the observation that ”r” in front of an ”s” is skipped in the particular dialect spoken in and around Jönköping. The first Thursday of March. Första torsdagen i mars, thus will be pronounciated Fössta tossdan i mass. Two years later somebody suggested that people from Jönköping could celebrate by eating a special cake with marzipan, in this special dialect massipantååta. 2010-2019 this celebration has exploded, on Facebook and also outside internet. Marzipan cakes are baked in all bakeries in Jönköping and surroundings, but the very last years also in other cities in Sweden. People with a background in Jönköping and the county of Småland offer their colleagues marzipan cake this very day, and everyone can follow the celebrations, pictures of cakes, special newly written songs and shows, on Facebook and other social media, like Instagram and Twitter. This is an example of how a dialect which has been used in films and other popular culture as a symbol of something rural, a little oldfashioned and embarrissing, is turned to something positive in a self- ironic and humoristic way. It is also an example of how a phenomenon – which might be shortlived, we do not know that yet - moves from the digital to the real world.